WAYS TO OPTIMIZE AND IMPROVE THE LEADER'S ACTIVITIES FOR ENSURING THE EFFICIENT MANAGEMENT OF A SPORTS ORGANIZATION. - CERNITOIU COSMIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
Sports management is a scientific branch that studies leadership types in institutionalized organizations of physical culture and sports orientation. Physical culture and sports have special means and methods for the directed development of people's physical capacity, beyond just being necessary motor activities. Sports entities such as sports schools, clubs, teams, stadiums, and federations are represented in management theory under physical culture. The concept of organization is essential in sports management, and an organization is a social system of deliberately coordinated activities of two or more people to achieve a common goal. Management is associated with complex organizations that have interdependent objectives and multifunctional activities